Silabel Ritmis: Pelafalan Alternatif dalam Pembelajaran Musik - Putra, Agung Dwi; Sinaga, Fajry Sub’haan Syah (Journal of Music Science, Technology, and Industry, 2021)
Purpose: This study aims to provide several kinds of rhythmic pronunciation in the process of music learning. Alternative pronunciation trials were carried out for music education students who were taking Music Theory courses. Research Method: This study uses a research-based design approach (dbr) with a qualitative paradigm. Results and discussion: The results of this study indicate several obstacles faced by students in rhythmic learning which are divided into four (4) sections: (1) obstacles in pronouncing the 8th and 32nd notes; (2) pronunciation of ta-ta-ta-ta in 32nd note; (3) lack of understanding of the ta-ta-ta-ta syllable in music theory learning; (4) students’ lack of understanding in associating sounds with notation. Implication: This research is expected to be an alternative reference in learning music, especially related to rhythm and syllables.